FINANCIAL MARKETS AND STOCK EXCHANGES, PROLETER A. D. BEČEJ AND OTHERS, SUBOTICA, 2009, S. 462 (PROF. MIROSLAV VITEZ, PH.D.) - M. Vunjak, Nenad; D. Kovačević, Ljubomir (Law - Theory and Practice, 2009)
-